KEWENANGAN DESA BERDASARKAN HAK ASAL USUL DALAM PERSPEKTIF HUKUM ADMINISTRASI - Arifin, Firdaus (Legal Standing : Jurnal Ilmu Hukum, 2024)
Regional autonomy in Indonesia grants villages the authority to manage their own government affairs, including authority based on origin rights derived from traditions, customs, and local history. However, the implementation of village authority often faces challenges within the framework of regional autonomy. This study aims to analyze and evaluate efforts to harmonize village authority based on origin rights with the principles of regional autonomy. Using a qualitative approach with case studies in several villages, this research found that strengthening village authority through clear and firm legality is the key to achieving optimal harmonization. This study illustrates how the dynamics of village authority grounded in indigenous rights can significantly contribute to the alignment of regional autonomy principles in Indonesia. The focus on legality is a crucial factor that can improve efficacy and accountability in village governance, while also bolstering community participation.